Centrosome and spindle function of the Drosophila Ncd microtubule motor visualized in live embryos using Ncd-GFP fusion proteins. - Endow, S.A.; Komma, D.J. (Journal of Cell Science, 1996)
The Ncd microtubule motor protein is required for meiotic and early mitotic chromosome distribution in Drosophila. Null mutant females expressing the Ncd motor fused to the Aequorea victoria green fluorescent protein (GFP), regulated by the wild-type ncd promoter, are rescued for chromosome segregation and embryo viability. Analysis of mitosis in live embryos shows cell cycle-dependent localization of Ncd-GFP to centrosomes and spindles. The distribution of Ncd-GFP in spindles during metaphase differs strikingly from that of tubulin: the tubulin staining is excluded by the chromosomes at the metaphase plate; in contrast, Ncd-GFP forms filaments along the spindle microtubules that extend across the chromosomes. The existence of Ncd-GFP fibers that cross the metaphase plate suggests that Ncd interacts functionally with chromosomes in metaphase. Differences are no longer observed in anaphase when the chromosomes have moved off the metaphase plate. A mutant form of Ncd fused to GFP also localizes to spindles in live embryos. Mutant embryos show frequent centrosome and spindle abnormalities, including free centrosomes that dissociate from interphase nuclei, precociously split centrosomes, and spindles with microtubule spurs or bridges to nearby spindles. The precociously split and free centrosomes indicate that the Ncd motor acts in cleavage stage embryos to maintain centrosome integrity and attachment to nuclei. The frequent spindle spurs of mutant embryos are associated with mis-segregating chromosomes that partially detach from the spindle in metaphase, but can be recaptured in early anaphase. This implies that the Ncd motor functions to prevent chromosome loss by maintaining chromosome attachment to the spindle in metaphase, consistent with the Ncd-GFP fibers that across the metaphase plate.